Editorial RBIE v.32 - Brandão, Anarosa; Araújo, Rafael; Souto Oliveira, Ana Liz; Boscarioli, Clodis; Maia, Dennys; Pimentel, Edson; Guarda, Graziela Ferreira; Costa, Newarney Torrezão da; Paiva, Ranilson; Sánchez-Reina, Roberto; Cazella, Sílvio; Odakura, Valguima (Revista Brasileira de Informática na Educação, 2024)
Prefácio, revisores e equipe editorial do volume 32, ano 2024.